The model of the long-term athlete development in the United States - Игорь Андреев; Юрий Павленко (National University of Physical Education and Sport of Ukraine, 2017)
A concept of the long-term athlete development created by the United States Olympic Committee and Governing Bodies of sport is introduced. The developed model is regarded as the basis for the development of American youth through sports activities and as the way to sustainable physical activity and healthy lifestyle, to athletic advancement and success at Olympic and Paralympic Games. The American Development Model is comprised of five stages. The model provides managers, trainers, parents, and athletes with guidelines for building and delivering programs that focus on developing the abilities of the individual athlete at each stage of long-term preparation.